Tongkat Aplikator Pestisida untuk Hama Kumbang Kelapa Sawit - Sutejo, Agus; Ramdani, Gilang; Putri, Amalia; Ferdiansyah, Bambang; Putra, Gregorios Damar Pratama; Assidiek, Mochammad Rizky (Jurnal Agricultural Biosystem Engineering, 2025)
Oil palm (Elaeis guineensis Jacq.) is one of Indonesia’s most important plantation commodities, yet its productivity is often hampered by the rhinoceros beetle (Oryctes rhinoceros L.). Conventional pest control methods using pesticide spraying are limited by uneven distribution, high risk of chemical exposure to workers, and pesticide wastage. This study designed a telescopic pesticide applicator stick as an innovation to improve pest control efficiency. The device consists of a 300 g capacity hopper, a stainless-steel auger, a 12V DC motor with gearbox, a 1.5–3 m aluminum telescopic pole, and a monostable mechanism based on an Arduino microcontroller to regulate pesticide dosage (5, 10, and 15 g). Mechanical analysis using Finite Element Analysis (FEA) showed that the telescopic clamp could withstand up to 300 N of load, while the elbow clamp could hold up to 600 N. Ergonomic analysis using the Rapid Entire Body Assessment (REBA) method produced a score of 5, indicating a medium risk level but still safe for operation. Functional testing revealed that the device was able to deliver granular pesticides precisely, with an effective spray reach of 20–30 cm from the outlet. The hopper capacity allowed application on approximately 30 trees per refill. With a production cost of around IDR 500,000, this innovation is considered effective, efficient, and economical in supporting oil palm rhinoceros beetle control while enhancing worker safety in the field.